RADIATION PROTECTION MEASURES TAKEN DURING REPATRIATION OF SEALED HIGH ACTIVITY RADIOACTIVE SOURCES IN CAMEROON. Issue 3 (5th August 2017) - Beyala Ateba, J F; Sabouang, J F; Simo, A; Moyo, M; Haieta, H
Abstract: Operational measures taken for the repatriation of Alcyon II 60 Co Teletherapy head and El Dorado 6 60 Co Teletherapy devices located in Yaounde and Douala respectively are reported. Operations carried out have permit to store Alcyon head in the CC 33 container and to transfer 60 Co source from El Dorado 6 device to YKT1B container. These containers are approved as Type B package for securely transport. Optically stimulated luminescence dosimeters had been distributed to all involved persons to estimate the received effective dose during operations. It appears by the present study that, the most received individual effective dose is 130 μSv during the whole process.